Fabrication, antioxidant, and optical properties of Poly(ε-caprolactone)/ metal oxide fibers by electroblowing - Huner, Azra; Sezer, Esma (ELSEVIER, 2026)
The properties of nanofibers (NFs), such as their aspect ratio, tensile strength, porosity, and the ability to combine organic-inorganic materials, make them important in biomedical applications, electronics, and optics. Several methods for the production of these NFs are still being developed, and electroblowing is one such method. This method allows for high yields in very short times, while also saving energy through the use of airflow. By utilizing the advantages of this method, metal oxide nanoparticle ()NFs will have the potential to be used in many applications, stimulating the production of new materials. In this study, poly(epsilon-caprolactone) (PCL)/MeONP NFs were produced via electroblowing using PCL obtained by deposition, along with copper oxide (CuO), iron oxide (FeOx), and manganese oxide (MnO) NPs. These fibers were characterized by FTIR, UV-Vis spectroscopy, XRD, TGA, DTG, DMA, SEM, and EDS analyses. These PCL/MeONP NFs were observed to have antioxidant properties by the 2,2 '-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay, and the highest antioxidant activity of 54.32 mu g TE/mg was obtained from PCL/CuO NFs. The estimated optical band gap of these nanofibers was calculated to be 2.41-2.82 eV. PCL and MeONPs are widely used as biomaterials, and the electroblown PCL/MeONP NFs presented for the first time in this study have the potential to be used as biomaterials in many biomedical applications.
Keywords: Poly(epsilon-caprolactone); Iron oxide; Copper oxide; Manganese oxide; Nanofiber; NANOPARTICLES; RAMAN; Materials Science; Physics